ANALISA KINEMATIKA DAN DEKOMPOSISI SISTEM GAYA PADA CDDR - Prahasto, Toni (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2010)
This article presents an elementary description about the characteristics of cable-direct-driverobot, in particular about the kinematic constraints and kinetics redundancy in cable driving system. Therobot that is observed in this article is one with three-cable driver; as a consequence, this robot will haveone redundancy. Robot’s motion lies on a plane, that is the planar curvilinear motion. Robot’s motion isassumed to be purely translational, and no rotation occurs. The redundancy is represented by a linearcombination of the range space and the multiple of null space of the coefficient matrix of the force systemat the end-effector. An example for a given position and a planar two-dimensional force system ispresented. The results indicate that the use of range space and null space together will produce statbleand consisten results